Review: Natural fiber-based biocomposites for potential advanced automotive applications - Sultan Ullah; Zeenat Akhter; Arvydas Palevicius; Giedrius Janusas (Journal of Engineered Fibers and Fabrics)
The search for novel materials for a variety of end-use applications has been encouraged by increased concern for the environment. This review offers a comprehensive analysis of biocomposites derived from natural resources, which have attracted considerable research interest. It focuses on key categories of biodegradable polymers and natural fibers, detailing their manufacturing processes, bonding mechanisms, and inherent properties. The paper emphasizes both physical and thermal features of different bio-based materials, particularly in automotive applications, and evaluates their compatibility with different matrix materials. Drawbacks and possibilities related to processing of biodegradable fiber-reinforced materials are explored, alongside a performance comparison with traditional materials commonly used in the automotive sector. The review concludes by addressing the economic implications and prospects of biocomposites, highlighting their potential as a rapidly emerging field in polymer science with significant applications within the vehicle sector.